Flexible solar cell and glass substrate and application thereof

By using an optimized sodium aluminosilicate flexible glass substrate in flexible solar cells, the problem of insufficient photoelectric conversion efficiency and mechanical stability of flexible perovskite solar cells is solved, and higher photoelectric conversion efficiency and better mechanical performance are achieved.

CN119774874APending Publication Date: 2025-04-08TUNGHSU TECH GRP CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411676709.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-04-08

AI Technical Summary

Technical Problem

The photoelectric conversion efficiency and mechanical stability of flexible perovskite solar cells have not yet met the industry standards, mainly due to the uncontrollable growth of polycrystalline perovskite films on flexible substrates and the inherent high Young's modulus.

Method used

A glass substrate for flexible solar cells is provided, including sodium aluminosilicate flexible glass, whose composition is optimized to ensure that the substrate has the same or similar thermal expansion coefficient as the battery material, can withstand the battery preparation process temperature, and has the characteristics of small surface roughness, light weight, low cost, etc.

Benefits of technology

By using an optimized sodium aluminosilicate flexible glass substrate, the photoelectric conversion efficiency of flexible solar cells is improved and its mechanical stability and durability are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119774874A_ABST
    Figure CN119774874A_ABST
Patent Text Reader

Abstract

The invention relates to a flexible solar cell and a glass substrate and application thereof, and belongs to the technical field of solar cells. The flexible sodium aluminosilicate glass is prepared from the following components: 55 percent to 62 percent of SiO2, 15 percent to 25 percent of Al2O3, 1 percent to 5 percent of B2O3, 10 percent to 14 percent of Na2O, 0.1 percent to 5 percent of K2O, 1 percent to 9 percent of MgO, 1 percent to 3 percent of ZnO, 0.1 percent to 2 percent of La2O3 and 0.5 percent to 2.5 percent of CeO2. Through mutual cooperation of all the components and adjustment and control of the content range of all the components, the glass substrate has the advantages of having the same or similar thermal expansion coefficient as a cell material, being capable of bearing the cell preparation process temperature, being small in surface roughness, light, low in cost and the like, and is suitable for preparing flexible solar cells. Therefore, the flexible solar cell has high photoelectric conversion efficiency and good portability and durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular to a flexible solar cell and a glass substrate and application thereof. Background Art

[0002] Thin-film solar cells can be prepared on metal foil and plastic substrates to form flexible solar cells. Flexible solar cells have the advantages of light weight, bendability, and easy to carry and transport. They can be used in defense and military fields such as satellites, airships, drones, and individual equipment, as well as civilian fields such as photovoltaic building integration and wearable smart devices, and have broad market prospects. Compared with traditional hard silicon-based solar cells, the advantages of flexible solar cells are mainly reflected in light weight, excellent mechanical properties, easy application, and easy mass production.

[0003] At present, flexible solar cells mainly include flexible silicon thin film solar cells, flexible copper indium gallium selenide solar cells, flexible cadmium telluride solar cells and flexible perovskite solar cells. Among them, flexible perovskite solar cells have the advantages of light weight and flexibility, are suitable for multi-scenario applications, and are the best candidate technology for traditional silicon solar cells in the photovoltaic market. However, its photoelectric conversion efficiency (PCE) and mechanical stability have not yet reached industry standards, mainly due to the uncontrollable growth of polycrystalline perovskite films on flexible substrates and the inherent high Young's modulus. First of all, the growth of perovskite films is highly sensitive to the substrate material. Flexible substrates with rough surfaces often induce a large number of nucleation sites, resulting in excessive crystallization and nucleation, resulting in small grain size of the grown perovskite and poor film morphology. In addition, polycrystalline perovskite films contain a large number of grain boundaries, which usually cause high Young's modulus, making the film more fragile under mechanical stress. The currently used organic flexible substrates are difficult to withstand high annealing temperatures (>150°C), and it is difficult to take advantage of the charge transfer characteristics of semiconductor films at low temperatures. In addition, compared with glass substrates, the plastic substrates used in flexible perovskite thin-film batteries have higher water vapor permeability, resulting in reduced device stability.

[0004] Therefore, the substrate of flexible solar cells needs to meet several conditions: have the same or similar thermal expansion coefficient as the battery material, be able to withstand the temperature of the battery preparation process, have a small surface roughness, be light, and have low cost. At present, the materials commonly used as flexible substrates are stainless steel foil, PI, PEN, and PET. Among them, stainless steel foil can withstand the temperature of the battery preparation process, but the surface roughness of the substrate is large, and the metal impurities in it will diffuse into the battery during the preparation process, affecting the battery efficiency; PI (CPI), PEN, and PET have small surface roughness and are lighter, but the temperature resistance level, high temperature dimensional stability, and water and oxygen barrier properties are all poor, and the glass transition temperature (Tg) is often less than 500°C. They cannot withstand high temperature processes, and the battery efficiency will be significantly affected. Summary of the invention

[0005] The present application provides a flexible solar cell and its glass substrate and application, so as to provide a substrate with good flexibility, high light transmittance and good heat resistance, so as to improve the photoelectric conversion efficiency and durability of the flexible solar cell.

[0006] In a first aspect, the present application provides a glass substrate for a flexible solar cell, the glass substrate comprising a sodium aluminum silicate flexible glass, wherein the composition of the sodium aluminum silicate flexible glass comprises, by mass percentage: SiO 2 :55%~62%,Al 2 O 3 :15%~25%, B 2 O 3 :1%~5%,Na 2 O: 10% to 14%, K 2 O: 0.1% to 5%, MgO: 1% to 9%, ZnO: 1% to 3%, La 2 O 3 :0.1%~2% and CeO 2 : 0.5% ~ 2.5%, and inevitable impurities.

[0007] As an optional embodiment, the composition of the sodium aluminum silicate flexible glass includes, by mass percentage:

[0008] SiO 2 The mass percentage is 57% to 61%; and / or

[0009] Al 2 O 3 The mass percentage is 18% to 23%; and / or

[0010] B 2 O 3 The mass percentage is 3% to 4.5%; and / or

[0011] Na 2 The mass percentage of O is 12% to 13%; and / or

[0012] K 2 The mass percentage of O is 0.8% to 3%; and / or

[0013] The mass percentage of MgO is 4% to 7%; and / or

[0014] The mass percentage of ZnO is 1.5% to 2%; and / or

[0015] La 2 O 3 The mass percentage is 0.4% to 1.5%; and / or

[0016] CeO 2 The mass percentage is 0.8% to 2%.

[0017] As an optional embodiment, the density of the sodium aluminum silicate flexible glass is lower than 2.50 g / cm 3 ; and / or

[0018] In the range of 50°C to 350°C, the thermal expansion coefficient of the sodium aluminum silicate flexible glass is (70-85)×10 -7 / ℃; and / or

[0019] The Young's modulus of the sodium aluminosilicate flexible glass is higher than 70 GPa; and / or

[0020] The glass transition temperature Tg of the sodium aluminosilicate flexible glass is higher than 600° C.; and / or

[0021] At 20°C, the sodium aluminum silicate flexible glass is subjected to 10% hydrofluoric acid corrosion for 20 minutes, and the corrosion amount is less than 15 mg / cm 2 ; and / or

[0022] At 95°C, the sodium aluminum silicate flexible glass is corroded by a sodium hydroxide solution with a mass concentration of 5% for 6 hours with a corrosion amount less than 2 mg / cm 2 .

[0023] As an optional embodiment, the thickness of the sodium aluminum silicate flexible glass is less than 0.1 mm; and / or

[0024] The bending radius of the sodium aluminosilicate flexible glass is less than 1 mm; and / or

[0025] The surface roughness Ra of the sodium aluminum silicate flexible glass is less than 1 nm; and / or

[0026] The sodium aluminum silicate flexible glass has a transmittance of ≥92% at 550nm; and / or

[0027] The transmittance of the sodium aluminum silicate flexible glass at 300 nm is less than 40%.

[0028] In a second aspect, the present application provides a glass substrate for a flexible solar cell, the glass substrate comprising a chemically strengthened sodium aluminum silicate flexible glass, the surface of the chemically strengthened sodium aluminum silicate flexible glass having a compressive stress layer, and the interior having a tensile stress layer, the composition at the center of the chemically strengthened sodium aluminum silicate flexible glass comprising, by mass percentage: SiO 2 :55%~62%,Al 2 O 3 :15%~25%, B 2 O3 :1%~5%,Na 2 O: 10% to 14%, K 2 O: 0.1% to 5%, MgO: 1% to 9%, ZnO: 1% to 3%, La 2 O 3 :0.1%~2% and CeO 2 : 0.5% ~ 2.5%, and inevitable impurities.

[0029] As an optional embodiment, the surface compressive stress of the chemically strengthened sodium aluminum silicate flexible glass exceeds 600 MPa; and / or

[0030] The thickness of the compressive stress layer exceeds 6 μm.

[0031] In a third aspect, the present application provides a flexible solar cell, wherein the flexible solar cell comprises the glass substrate provided in the first aspect or the second aspect.

[0032] As an optional implementation, the bending radius of the flexible solar cell is less than 4 mm; and / or

[0033] The photoelectric conversion efficiency of the flexible solar cell is greater than 15%.

[0034] As an optional implementation, the photoelectric conversion efficiency of the flexible solar cell remains above 90% of the initial value after being bent 1000 times at a bending radius of 4 mm.

[0035] In a fourth aspect, the present application provides a photovoltaic module, comprising the flexible solar cell provided in the third aspect.

[0036] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:

[0037] The glass substrate provided in the embodiment of the present application has the same or similar thermal expansion coefficient as the battery material through the mutual coordination of various components and the adjustment and control of the content range of various components. The glass substrate can withstand the temperature of the battery preparation process and has the characteristics of small surface roughness, light weight, low cost, etc. It is suitable for preparing flexible solar cells, so that the flexible solar cells have higher photoelectric conversion efficiency and better lightness and durability. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the present application and, together with the description, serve to explain the principles of the present application.

[0039] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0040] Figure 1 A schematic diagram of the structure of a flexible solar cell provided in an embodiment of the present application.

[0041] Figure numerals: 1 - substrate, 2 - transparent conductive layer, 3 - light absorption layer, 4 - electron transport layer, 5 - hole transport layer, 6 - reflection layer, 7 - counter electrode. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0043] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.

[0044] The present invention provides a glass substrate for a flexible solar cell, wherein the glass substrate comprises a sodium aluminum silicate flexible glass, and the components of the sodium aluminum silicate flexible glass include, by mass percentage: SiO 2 :55%~62%,Al 2 O 3 :15%~25%, B 2 O 3 :1%~5%,Na 2 O: 10% to 14%, K 2 O: 0.1% to 5%, MgO: 1% to 9%, ZnO: 1% to 3%, La 2 O 3 :0.1%~2% and CeO 2 : 0.5% ~ 2.5%, and inevitable impurities.

[0045] In some embodiments, the composition of the sodium aluminum silicate flexible glass includes, by weight percentage: 57-61 wt % SiO 2 , 18-23wt% Al 2 O 3 3-4.5wt% B2 O 3 , 12-13wt% Na 2 O, 0.8-3wt% K 2 O, 4-7wt% MgO, 1.5-2wt% ZnO, 0.4-1.5wt% La 2 O 3 0.8-2wt% CeO 2 .

[0046] In this application, SiO 2 As a matrix that forms a network structure, its addition can improve the heat resistance and chemical durability of glass, make the glass less likely to lose transparency, and also help the vitrification process. 2 The melting temperature will increase, the brittleness will increase, and the production process will be too demanding. The inventors further found in their research that, in terms of mass percentage, SiO 2 When the content of SiO2 is ≥40wt%, the mechanical properties, thermal stability and chemical corrosion resistance of the prepared glass can be further improved. If the content is too high, the flexibility of the glass will be reduced. Therefore, in order to further improve the comprehensive performance of the prepared glass, preferably, in terms of mass percentage, 55wt%≤SiO2 2 ≤62wt%. Further preferably, in terms of mass percentage, 57wt%≤SiO 2 ≤61wt%.

[0047] In this application, Al 2 O 3 The addition of can promote the integrity of network connection, greatly improve the heat resistance, ion exchange depth and surface compressive stress, mechanical stability, fracture toughness and bending performance of glass, but at the same time it will make the glass structure tend to be rigid, increase the brittleness of glass, and make the glass easy to lose transparency, high temperature surface tension and high temperature viscosity are too large, increase the difficulty of glass production process, etc. Comprehensive consideration, based on the weight of the composition, calculated as oxide, Al 2 O 3 The content of Al is in the range of 15-25wt%. Further preferably, in terms of mass percentage, 18wt%≤Al 2 O 3 ≤23wt%.

[0048] In this application, B 2 O 3 As the matrix of borosilicate glass, it can generate glass alone. Its addition can reduce the brittleness of glass and improve the fracture toughness of glass. 2 O 3 It is also a good co-solvent, which can significantly reduce the melting temperature of glass and is also beneficial to the vitrification process.4 ]tetrahedron and [BO 3 ] Two triangular structures, B under high temperature melting conditions 2 O 3 Difficult to form [BO 4 ], which can reduce high temperature viscosity, and at low temperatures, it preferentially forms tetrahedrons or triangles depending on the amount of free oxygen. In borosilicate glass, [BO 4 ]tetrahedron can be combined with [SiO 4 ]tetrahedrons form a unified continuous three-dimensional network, while [BO 3 The triangles are connected by rotatable boron rings, which slip when subjected to force, resulting in plastic rheology, low brittleness and high fracture toughness; and borosilicate glass has a low melting point, and the temperature corresponding to the viscosity of 200 poise (T 2.3 ) is lower than 1450℃ and lower. At the same time, borosilicate glass has lower high-temperature surface tension than high-aluminosilicate glass and is more suitable for mass industrial production. However, excessive B 2 O 3 The low temperature viscosity of the glass will be reduced, which is not conducive to the subsequent chemical tempering process adjustment. 2 O 3 The content is 1-5wt%, preferably 3-4.5wt%.

[0049] In this application, Na + , K + It is an ion exchange component. Properly increasing its content can effectively reduce the high-temperature viscosity of the glass, thereby improving its melting and formability, and improving devitrification. At the same time, the introduction of Na + , K + Under such circumstances, the mixed alkali effect can more effectively reduce the high temperature viscosity and increase the liquidus viscosity, which is beneficial to the quality adjustment of the industrial production line, the improvement of yield and the reduction of cost. However, too high a content will increase the thermal expansion of the glass and reduce the chemical durability, thermal stability and mechanical stability of the glass, and too high a content will tend to deteriorate the devitrification. Therefore, in order to further improve the comprehensive performance of the prepared glass, preferably, based on the weight of the composition, calculated as oxide, 10wt%≤Na 2 O≤14wt%; further preferably, 0.1wt%≤K 2 O≤5wt%.

[0050] In the present application, MgO belongs to alkaline earth metal oxides. Their addition can effectively reduce the high temperature viscosity of glass, thereby improving the solubility and formability of glass, and can accelerate the ion exchange process of glass. MgO has the characteristics of improving the thermal stability of glass and reducing brittleness. Excessive content will increase the density, and the incidence of cracks, devitrification, and phase separation will increase. Therefore, taking all factors into consideration, based on the weight of each component, it contains 1-9wt% of MgO. Preferably, based on the weight of the composition, in terms of oxide, 4wt%≤MgO≤7wt%.

[0051] Divalent metal oxides can be divided into two categories according to their position in the periodic table and their influence on properties: one is the alkaline earth metal oxides in the main group, whose ions R 2+ It has 8 outer electrons; the second type is located in the subgroup of the periodic table (such as ZnO, CdO, etc.), and its ion R 2+ With 18 outer electrons, the structural states of the two in glass and their effects on glass properties are different. 2+ Ions are more easily polarized, which can reduce the viscosity of the glass at high temperatures (such as 1450°C), which is conducive to eliminating bubbles; when the total alkali content and the molecular ratio of the network intermediate oxide are greater than 1, Zn is introduced into the glass as a network foreign body. 2+ Tends to form tetrahedrons with four coordination [ZnO 4 ] exists, compared with [ZnO 6 ] The glass structure is looser. In the present application, ZnO is introduced. Compared with the glass without ZnO under the same high temperature state, the glass containing ZnO has a smaller viscosity and a faster atomic movement speed, and cannot form a crystal nucleus. The temperature needs to be further lowered to facilitate the formation of the crystal nucleus. Therefore, the upper limit temperature of crystallization of the glass is reduced; below the softening point, it has the effect of improving the strength and hardness, increasing the chemical resistance of the glass, reducing the brittleness value, and reducing the thermal expansion coefficient of the glass. Excessive ZnO content will greatly reduce the strain point of the glass. Therefore, taking all factors into consideration, the content of ZnO is 1-3wt%, preferably 1.5-2wt%, based on the weight of the composition.

[0052] In this application, the rare earth oxide La 2 O 3 They often have unique abilities to improve certain properties of glass. For example, the flexural strength, elastic modulus, strain point and other properties of glass increase significantly with the addition of rare earth oxides, which reduces the brittleness of glass and significantly increases its fracture toughness. After alkaline earth metals, ZnO and other network exogenous bodies are introduced into the glass composition, the excess oxygen atoms cause the bridging oxygen bonds in the glass structure to break and generate non-bridging oxygen. The presence of these non-bridging oxygen atoms significantly reduces the flexural strength of glass. 2 O 3The addition of La causes the internal structure of the glass to change. The generated Si-O-La chemical bonds reconnect the isolated island network units in the glass, improving the network structure of the glass, thereby greatly improving the bending strength, elastic modulus, strain point and other properties of the glass. 2 O 3 When the amount of non-bridging oxygen available for adjustment is reduced, the above-mentioned properties of the glass do not change much. Therefore, taking all factors into consideration, based on the weight of the composition, La 2 O 3 The content is 0.1-2wt%, preferably 0.4-1.5wt%.

[0053] In this application, CeO 2 It can improve the ultraviolet absorption characteristics of glass. When solar cells are exposed to ultraviolet rays in sunlight for a long time, color centers will be generated. These color centers will produce new absorption bands in the visible light band, thereby reducing the power generation efficiency of the battery. In order to improve the anti-ultraviolet performance of glass, a certain amount of variable valence oxides are usually added to the base glass to prevent the generation of color centers. A large number of experiments have shown that adding stabilizers to the base glass can improve the ultraviolet absorption performance of the glass. The mechanism of action of the stabilizer is mainly that it can compensate for the local electron-nuclear imbalance caused by electrons and vacancies, thereby inhibiting the formation of color centers in the glass and reducing the ultraviolet aging damage of the glass. The effect of cerium oxide on improving the ultraviolet absorption performance of glass can be expressed by the equation Ce: 4+ +e=Ce 3+ According to the requirements of ultraviolet absorption performance and spectral transmittance performance, this application CeO 2 The content is 0.5-2.5%, preferably 0.8-2%. 4+ There is a change in price at high temperature 3+ The situation plays a role in regulating the gas partial pressure during the glass melting process, thereby causing changes in the partial pressure of each component in the residual bubbles, promoting the growth and floating of the bubbles until they are eliminated, and playing the role of a chemical clarifier. Therefore, the glass of the present invention no longer requires additional chemical clarifiers.

[0054] The glass substrate has the same or similar thermal expansion coefficient as the battery material through the mutual coordination of various components and the adjustment and control of the content range of various components. It can withstand the temperature of the battery preparation process and has the characteristics of small surface roughness, light weight, low cost, etc. It is suitable for preparing flexible solar cells, so that the flexible solar cells have higher photoelectric conversion efficiency and better lightness and durability.

[0055] In some embodiments, the density of the sodium aluminosilicate flexible glass is less than 2.50 g / cm 3In the range of 50℃~350℃, the thermal expansion coefficient of the sodium aluminum silicate flexible glass is (70-85)×10 -7 / ℃; the Young's modulus of the sodium aluminum silicate flexible glass is higher than 70GPa; the glass transition temperature Tg of the sodium aluminum silicate flexible glass is higher than 600℃; at 20℃, the corrosion amount of the sodium aluminum silicate flexible glass in 10% hydrofluoric acid corrosion for 20min is less than 15mg / cm 2 At 95°C, the sodium aluminum silicate flexible glass is corroded by a 5% sodium hydroxide solution for 6 hours with a corrosion amount of less than 2 mg / cm 2 .

[0056] In some embodiments, the thickness of the sodium aluminum silicate flexible glass is less than 0.1 mm; preferably, preferably, the thickness is less than 0.07 mm; further preferably, the thickness is less than 0.05 mm; and further preferably, the thickness is less than 0.03 mm. The bending radius of the sodium aluminum silicate flexible glass is less than 1 mm; further preferably, the bending radius is less than 0.7 mm; and further preferably, the bending radius is less than 0.4 mm. The surface roughness Ra of the sodium aluminum silicate flexible glass is less than 1 nm; further preferably, the surface roughness Ra is less than 0.7 nm; and further preferably, the surface roughness Ra is less than 0.4 nm. The transmittance of the sodium aluminum silicate flexible glass at 550 nm is ≥ 92%; further preferably, the transmittance at 550 nm is ≥ 93%. The transmittance of the sodium aluminum silicate flexible glass at 300 nm is less than 40%; further preferably, the transmittance at 300 nm is less than 20%; and further preferably, the transmittance at 300 nm is less than 20%.

[0057] The glass substrate has good performance in the above properties, providing a basis for flexible solar cells to have higher photoelectric conversion efficiency, as well as better lightness and durability.

[0058] The sodium aluminum silicate flexible glass provided above can be chemically strengthened, specifically by sodium potassium ion exchange. After chemical strengthening, the chemically strengthened sodium aluminum silicate flexible glass is obtained. The surface of the chemically strengthened sodium aluminum silicate flexible glass has a compressive stress layer and the inside has a tensile stress layer. The components at the center of the chemically strengthened sodium aluminum silicate flexible glass include, by mass percentage: SiO 2 :55%~62%,Al 2 O 3 :15%~25%, B 2 O 3 :1%~5%,Na 2 O: 10% to 14%, K 2 O: 0.1% to 5%, MgO: 1% to 9%, ZnO: 1% to 3%, La2 O 3 :0.1%~2% and CeO 2 :0.5%~2.5%, and unavoidable impurities. Chemically strengthened sodium aluminum silicate flexible glass can have better performance.

[0059] In some embodiments, the surface compressive stress of the chemically strengthened sodium aluminosilicate flexible glass exceeds 600 MPa; and the thickness of the compressive stress layer exceeds 6 μm.

[0060] Figure 1 The schematic diagram of the structure of the flexible solar cell provided in the embodiment of the present application is as follows: Figure 1 As shown, based on a general inventive concept, an embodiment of the present application further provides a flexible solar cell, wherein the flexible solar cell includes the glass substrate provided above.

[0061] The flexible solar cell is realized based on the above-mentioned glass substrate. The specific content of the glass substrate can refer to the above-mentioned embodiment. Since the flexible solar cell adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0062] In some embodiments, the bending radius of the flexible solar cell is less than 4 mm; more preferably, the bending radius is less than 3 mm, and more preferably, the bending radius is less than 2 mm; and more preferably, the bending radius is less than 1 mm. The photoelectric conversion efficiency of the flexible solar cell is greater than 15%. Preferably, the photoelectric conversion efficiency is greater than 18%. More preferably, the photoelectric conversion efficiency is greater than 20%. More preferably, the photoelectric conversion efficiency is greater than 21%.

[0063] In some embodiments, the photoelectric conversion efficiency of the flexible solar cell remains above 90% of the initial value after being bent 1000 times at a bending radius of 4 mm. Preferably, it remains above 90% of the initial value after being bent 1000 times at a bending radius of 3 mm. Further preferably, it remains above 90% of the initial value after being bent 1000 times at a bending radius of 2 mm. Even further preferably, it remains above 90% of the initial value after being bent 1000 times at a bending radius of 1 mm.

[0064] In some embodiments, the specific structure of the flexible solar cell may include a substrate, a transparent conductive layer, a light absorbing layer, an electron transport layer, a hole transport layer, a reflective layer, and a counter electrode.

[0065] The substrate is the glass substrate provided above.

[0066] The transparent conductive layer may be a transparent conductive oxide (TCO) layer prepared on the surface of the flexible glass substrate, which can improve the conductivity and electron mobility. A transparent bottom electrode is arranged on the transparent conductive oxide (TCO) layer, and the transparent bottom electrode includes at least one of silver nanowires (Ag-NWs), aluminum-doped zinc oxide (AZO), carbon nanotubes (CNT), graphene, and organic molecules (including but not limited to PEDOT:PSS).

[0067] The light absorption layer can use a new type of perovskite material with a thickness of 200nm to 500nm, which has excellent light absorption performance. Among them, perovskite material refers to organic-inorganic hybrid semiconductor materials, which have the advantages of strong absorption capacity, high electron mobility, long charge life, adjustable band gap, and can be processed in a variety of ways. Its chemical formula is ABX 3 , generally an octahedral or cubic structure. In the ABX3 structured perovskite light absorbing material, A represents a monovalent organic cation (CH 3 NH 3 + , NH 2 CH=NH 2 + ), B represents a divalent metal cation (Pb 2+ , Sn 2+ ), X represents at least one of a halogen anion (I - , Cl - and Br - ). Perovskite light absorbing materials can simultaneously complete important processes such as the excitation, transportation, and separation of photogenerated charges. The main reason is that the perovskite light absorbing materials and the charge transport materials have a good energy level match, so that the electrons and holes generated by the perovskite layer after illumination can be effectively separated and quickly transferred, which plays a decisive role in realizing efficient flexible perovskite solar cells.

[0068] The electron transport layer can be made of metal oxide and / or organic material with a thickness of 30nm to 100nm to improve the electron transport efficiency. The material includes TiO 2 SnO 2 、ZnO、ZnSO 4 , Nb 2 O 5 , PCBM, C60, CDIN, ss-IL and synthetic organic small molecules. The electron transport layer film can be a one-layer, two-layer or multi-layer structure.

[0069] The hole transport layer may be made of polymer-based materials, including PEDOT:PSS, modified PTAA, with a thickness of 50nm to 150nm, to enhance the hole transport capability.

[0070] The reflective layer is an aluminum film with a thickness of 100nm set at the bottom of the battery, which can effectively reflect unabsorbed light and improve light utilization.

[0071] The counter electrode is a layer of counter electrode prepared on the surface of the hole transport layer or the electron transport layer. The counter electrode material can be Au and / or Ag prepared by thermal evaporation and / or magnetron sputtering under vacuum conditions. The counter electrode can be a multilayer MoOx / Ag / MoOx film.

[0072] In some embodiments, the preparation process of the flexible solar cell may be:

[0073] 1. Flexible substrate processing: Clean and surface treat the flexible glass substrate to improve adhesion.

[0074] 2. Transparent conductive layer deposition: Deposit a transparent bottom electrode on a flexible substrate using a solution method, evaporation method or magnetron sputtering method.

[0075] 3. Deposition of light absorption layer: The perovskite light absorption layer is deposited on the substrate by solution method or evaporation method, and the thickness is controlled between 200nm and 500nm.

[0076] 4. Electron transport layer deposition: Deposition of metal oxides and / or organic materials on the light absorbing layer using solution method, evaporation method or magnetron sputtering method to ensure uniformity and thickness control.

[0077] 4. Hole transport layer deposition: The hole transport layer is deposited on the electron transport layer using a spin coating method.

[0078] 5. Reflective layer deposition: Finally, an aluminum film is deposited at the bottom of the entire structure to form a reflective layer.

[0079] 6. Packaging processing: Packaging the prepared flexible perovskite thin-film solar cells to ensure their weather resistance and stability.

[0080] Based on a general inventive concept, an embodiment of the present application further provides a photovoltaic module, which includes the flexible solar cell provided above.

[0081] The photovoltaic module is realized based on the above-mentioned flexible solar cell. The specific content of the flexible solar cell can refer to the above-mentioned embodiment. Since the photovoltaic module adopts part or all of the technical solutions of the above-mentioned embodiments, it at least has all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be described one by one here.

[0082] The photovoltaic modules can be applied to defense and military fields such as satellites, airships, drones, and individual equipment, as well as photovoltaic building integration, wearable smart devices, smart grids, housing energy supply, commuter electric vehicles, household electronic products, solar charging and energy storage systems, and other fields.

[0083] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.

[0084] Examples and Comparative Examples

[0085] The composition (in mass percentage) of the glass substrates provided in the embodiments and comparative examples is shown in Table 1.

[0086] Table 1

[0087]

[0088]

[0089] The preparation process is to configure the raw materials according to the proportion of each oxide in the above table, the total mass of the configured raw materials is 1000g, and 5g of clarifier sodium chloride (NaCl) is added to the configured raw materials, and then mixed with a V-type mixer at a speed of 25r / min for more than 30 minutes to obtain a uniform raw material mixture.

[0090] The mixed raw material mixture is transferred to a platinum crucible, and then melted in a platinum-rhodium crucible at 1600°C for more than 5 hours, and then poured into a molding mold for molding and cooling. When it cools to about 900°C, it is then placed in a 460°C annealing furnace for annealing for 12 hours, and then cooled to room temperature with the furnace to obtain a glass substrate with a thickness of 0.03 mm.

[0091] Test the performance of the glass substrate.

[0092] Density test: Refer to ASTM C-693 to measure the glass density, the unit is g / cm 3 .

[0093] Thermal expansion coefficient test: refer to ASTM E-228 to measure the thermal expansion coefficient of glass at 50-350℃, the unit is 10 -7 / ℃.

[0094] Young's modulus test: The Young's modulus of glass is measured according to ASTM C-623, and the unit is GPa.

[0095] Glass transition temperature test: The glass transition temperature Tg was determined according to ASTM E-228.

[0096] Corrosion resistance test: At 20°C, the weight loss of glass per unit area after being immersed in a 10 wt% HF solution for 20 minutes is recorded as C HF , unit is mg / cm 2 The weight lost by a unit area of ​​glass after being immersed in a 95 wt% NaOH solution for 6 hours at 95°C water bath is recorded as C. NaOH , unit is mg / cm 2 .

[0097] Bending radius detection: Use a two-point bending tester to test the bending radius in mm.

[0098] Surface roughness Ra detection: Use a contact roughness tester to test the surface roughness, and use Ra to characterize the roughness.

[0099] Transmittance detection: The glass transmittance was measured using a UV-visible spectrophotometer (Perkin Elmer, model LAMBDA25), in %.

[0100] The results are shown in Table 2.

[0101] Table 2

[0102]

[0103]

[0104] The glass substrates provided in each embodiment and comparative example were prepared into flexible solar cells, specifically, a 300nm thick perovskite light absorption layer, a 30nm thick ZnO electron transport layer, and a 100nm thick modified PTAA polymer hole transport layer were sequentially deposited on the glass substrate. The performance of the flexible solar cells prepared from the glass substrates provided in each embodiment and comparative example was tested.

[0105] Conversion efficiency test: Refer to GB / T 39857-2021 to test the fixed-length photoelectric conversion efficiency.

[0106] Bending radius detection: Use a two-point bending tester to test the bending radius in mm.

[0107] The results are shown in Table 3.

[0108] Table 3

[0109]

[0110] It can be seen from Table 3 that the flexible solar cell prepared using the glass substrate provided in the embodiment of the present application has a higher photoelectric conversion efficiency and has good lightness and durability.

[0111] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0112] In the present application, in the absence of any contrary description, the directional words used, such as "upper" and "lower", are specifically the directions of the drawings in the accompanying drawings. In addition, in the description of the present specification, the terms "including", "comprising", etc. refer to "including but not limited to". In this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply that there is any such actual relationship or order between these entities or operations. In this article, "and / or" describes the association relationship of the associated objects, indicating that there may be three relationships, for example, A and / or B, which can represent: A exists alone, A and B exist at the same time, and B exists alone. Wherein A, B can be singular or plural. In this article, "at least one" refers to one or more, and "plural" refers to two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of singular or plural items. For example, "at least one of a, b or c" or "at least one of a, b and c" can both mean: a, b, c, a-b (i.e. a and b), a-c, b-c, or a-b-c, where a, b and c can be single or multiple.

[0113] The above description is only a specific implementation of the present application, so that those skilled in the art can understand or implement the present application. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein can be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application will not be limited to the embodiments shown herein, but will conform to the widest range consistent with the principles and novel features applied for herein.

Claims

1. A glass substrate for a flexible solar cell, characterized in that: The glass substrate includes sodium aluminum silicate flexible glass, and the components of the sodium aluminum silicate flexible glass include, by mass percentage, SiO2: 55% to 62%, Al2O3: 15% to 25%, B2O3: 1% to 5%, Na2O: 10% to 14%, K2O: 0.1% to 5%, MgO: 1% to 9%, ZnO: 1% to 3%, La2O3: 0.1% to 2% and CeO2: 0.5% to 2.5%, and inevitable impurities.

2. The glass substrate for a flexible solar cell according to claim 1, characterized in that: The composition of the sodium aluminum silicate flexible glass includes, by mass percentage: The mass percentage of SiO2 is 57% to 61%; and / or The mass percentage of Al2O3 is 18% to 23%; and / or The mass percentage of B2O3 is 3% to 4.5%; and / or The mass percentage of Na2O is 12% to 13%; and / or The mass percentage of K2O is 0.8% to 3%; and / or The mass percentage of MgO is 4% to 7%; and / or The mass percentage of ZnO is 1.5% to 2%; and / or The mass percentage of La2O3 is 0.4% to 1.5%; and / or The mass percentage of CeO2 is 0.8% to 2%.

3. The glass substrate for a flexible solar cell according to claim 1 or 2, characterized in that: The density of the sodium aluminum silicate flexible glass is lower than 2.50 g / cm 3 ; and / or In the range of 50°C to 350°C, the thermal expansion coefficient of the sodium aluminum silicate flexible glass is (70-85)×10 -7 / ℃; and / or The Young's modulus of the sodium aluminosilicate flexible glass is higher than 70 GPa; and / or The glass transition temperature Tg of the sodium aluminosilicate flexible glass is higher than 600° C.; and / or At 20°C, the sodium aluminum silicate flexible glass is subjected to 10% hydrofluoric acid corrosion for 20 minutes, and the corrosion amount is less than 15 mg / cm 2 ; and / or At 95°C, the sodium aluminum silicate flexible glass is corroded by a sodium hydroxide solution with a mass concentration of 5% for 6 hours with a corrosion amount less than 2 mg / cm 2 .

4. The glass substrate for a flexible solar cell according to claim 1 or 2, characterized in that: The thickness of the sodium aluminosilicate flexible glass is less than 0.1 mm; and / or The bending radius of the sodium aluminosilicate flexible glass is less than 1 mm; and / or The surface roughness Ra of the sodium aluminum silicate flexible glass is less than 1 nm; and / or The sodium aluminum silicate flexible glass has a transmittance of ≥92% at 550nm; and / or The transmittance of the sodium aluminum silicate flexible glass at 300 nm is less than 40%.

5. A glass substrate for a flexible solar cell, characterized in that: The glass substrate includes chemically strengthened sodium aluminum silicate flexible glass, the surface of the chemically strengthened sodium aluminum silicate flexible glass has a compressive stress layer, and the interior has a tensile stress layer, and the components at the center of the chemically strengthened sodium aluminum silicate flexible glass include, by mass percentage, SiO2: 55% to 62%, Al2O3: 15% to 25%, B2O3: 1% to 5%, Na2O: 10% to 14%, K2O: 0.1% to 5%, MgO: 1% to 9%, ZnO: 1% to 3%, La2O3: 0.1% to 2% and CeO2: 0.5% to 2.5%, and inevitable impurities.

6. The glass substrate for a flexible solar cell according to claim 5, characterized in that: The surface compressive stress of the chemically strengthened sodium aluminosilicate flexible glass exceeds 600 MPa; and / or The thickness of the compressive stress layer exceeds 6 μm.

7. A flexible solar cell, characterized in that: The flexible solar cell comprises the glass substrate according to any one of claims 1 to 6.

8. The flexible solar cell according to claim 7, characterized in that: The bending radius of the flexible solar cell is less than 4 mm; and / or The photoelectric conversion efficiency of the flexible solar cell is greater than 15%.

9. The flexible solar cell according to claim 7, characterized in that: The photoelectric conversion efficiency of the flexible solar cell is maintained at more than 90% of the initial value after being bent 1000 times at a bending radius of 4 mm.

10. A photovoltaic module, characterized in that: The photovoltaic module comprises the flexible solar cell according to any one of claims 7 to 9.

Citation Information

Cited By

  • Large-area flexible perovskite solar cell and preparation method thereof

    CN121815880A